2012
DOI: 10.1002/hep.25722
|View full text |Cite
|
Sign up to set email alerts
|

Immediate intraportal transplantation of human bone marrow mesenchymal stem cells prevents death from fulminant hepatic failure in pigs

Abstract: The effectiveness of human bone marrow mesenchymal stem cell (hBMSC) transplantation to treat acute and chronic liver injury has been demonstrated in animal models and in a few nonrandomized clinical trials. However, no studies have investigated hBMSC transplantation in the treatment of fulminant hepatic failure (FHF), especially in large animal (pig) models. The aim of this study was to demonstrate the safety, effectiveness, and underlying mechanism of hBMSC transplantation for treating FHF in pigs through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(112 citation statements)
references
References 33 publications
3
107
1
1
Order By: Relevance
“…Recently, studies have demonstrated that BMSCs reinforce liver regeneration and have significant suppressive effects on hepatocyte apoptosis (36)(37)(38). BMSCs suppress proapoptotic protein expression and enhance anti-apoptotic protein expression, consequently attenuating hepatocyte degeneration and subsequent apoptosis, as well as accelerating hepatocyte regeneration (39).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have demonstrated that BMSCs reinforce liver regeneration and have significant suppressive effects on hepatocyte apoptosis (36)(37)(38). BMSCs suppress proapoptotic protein expression and enhance anti-apoptotic protein expression, consequently attenuating hepatocyte degeneration and subsequent apoptosis, as well as accelerating hepatocyte regeneration (39).…”
Section: Discussionmentioning
confidence: 99%
“…ALF was induced with D-galactosamine, as described previously by our laboratory [29][30][31][32]. Animals were fasted for 8 hours prior to catheterisation.…”
Section: D-galactosamine-induced Alf Modelmentioning
confidence: 99%
“…This strategy possesses more significant potential for liver tissue engineering compared with hepatocytes or cells from embryos, because of its easy accessibility, rapid proliferation, multipotent differentiation, and immunological tolerance. [17][18][19] Several studies [20][21][22][23] have also showed that transplantation of BMSCs or BMSC-derived hepatocytes could improve the liver function in laboratory animals or patients suffering from liver damage.…”
Section: Introductionmentioning
confidence: 99%